ANALISIS KEMAMPUAN PENALARAN MATEMATIK SISWA SMP PADA SOAL-SOAL MATERI SEGI EMPAT DAN SEGITIGA - Puji Astuti; Ratna Sariningsih (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research aims to determine the ability of mathematical reasoning of students of class VIII SMP about the rectangular and triangular material. The research method used is descriptive qualitative research. Subjects in this study were 30 students in one junior high school in Cianjur District. The reasoning ability reasoning instrument used is an essay form. Indicator used in this research there are 7 indicators of reasoning ability that is drawing logical conclusion; provide explanations using images; establishing direct proof, indirect proof, and by proving by mathematical induction; filed the infringement rules, checked the validity of the arguments and compiled a valid argument; propose opponent example; estimate answers and solution processes; using relationship patterns to analyze, make analogies, generalizations, and compile and test conjectures.